Aluminum in liver cells – the element species matters. Issue 7 (9th August 2019) - Sieg, Holger; Ellermann, Anna Lena; Maria Kunz, Birgitta; Jalili, Pégah; Burel, Agnès; Hogeveen, Kevin; Böhmert, Linda; Chevance, Soizic; Braeuning, Albert; Gauffre, Fabienne; Fessard, Valérie; Lampen, Alfonso
Abstract: Aluminum (Al) can be ingested from food and released from packaging and can reach key organs involved in human metabolism, including the liver via systemic distribution. Recent studies discuss the occurrence of chemically distinct Al-species and their interconversion by contact with biological fluids. These Al species can vary with regard to their intestinal uptake, systemic transport, and therefore could have species-specific effects on different organs and tissues. This work aims to assess the in vitro hepatotoxic hazard potential of three different relevant Al species: soluble AlCl3 and two nanoparticulate Al species were applied, representing for the first time an investigation of metallic nanoparticles besides to mineral bound γ-Al2 O3 on hepatic cell lines. To investigate the uptake and toxicological properties of the Al species, we used two different human hepatic cell lines: HepG2 and differentiated HepaRG cells. Cellular uptake was determined by different methods including light microscopy, transmission electron microscopy, side-scatter analysis, and elemental analysis. Oxidative stress, mitochondrial dysfunction, cell death mechanisms, and DNA damage were monitored as cellular parameters. While cellular uptake into hepatic cell lines occurred predominantly in the particle form, only ionic AlCl3 caused cellular effects. Since it is known, that Al species can convert one into another, and mechanisms including 'trojan-horse'-like uptake can lead to an Al accumulation in the cells. This could result in the slow release of Al ions, for which reason further hazard cannot be excluded. Therefore, individual investigation of the different Al species is necessary to assess the toxicological potential of Al particles.